The use of Wordwall as an Evaluation Medium for Deaf Children at SLBN 1 Kulon Progo - Salsabila, Unik Hanifah; Andini, Rahmah Ayu; Istighfarin, Devina; Salsabila, Nisa; Jannah, Ulil (MO.RI Publishing, 2023)
The rapid advancement of technology in contemporary times necessitates the involvement of Islamic Education (PAI) teachers in maximizing the use of technological resources. PAI teachers are required to exhibit creativity in conducting evaluations using specific software or applications. This research aims to motivate PAI teachers by elucidating the steps involved in utilizing Wordwall as an evaluative medium and by discussing the advantages and limitations of Wordwall in assessing the learning of prayer movements at SLBN 1 Kulon Progo. Furthermore, this study is intended to serve as a novel innovation by leveraging modern technology to simplify the evaluation process in education. The methodology employed in this research is qualitative, with a descriptive approach and data collection techniques encompassing observation, interviews, and documentation. The research is further developed through field studies that reference journals and related sources. The findings reveal that the implementation of the Wordwall medium for educational evaluation assists and facilitates teachers in assessing the prayer movements of deaf children. The use of Wordwall as an evaluative tool positively impacts deaf students by simplifying their task completion, primarily through the use of predominantly image-based content with minimal text. It is hoped that with technological advancements, the scope of educational evaluation will become more varied and easier for teachers in assessing student learning outcomes. This study is conducted to contribute to the development of evaluative media that simplify teachers' tasks in assessing children's learning outcomes.